Compétences linguistiques et culturelles des organisations de santé. Analyse critique de la littérature - Aucoin, Léonard (InfoVeille Santé, 2008)

Les minorités francophones hors Québec et la gouvernance des langues officielles : portrait et enjeux - Cardinal, Linda; Lang, Stéphanie; Sauvé, Anik (Francophonies d'Amérique, 2008)
L’article porte sur l’évolution des formes et des rapports de gouvernance entre le gouvernement fédéral et les communautés minoritaires de langue officielle au Canada. La gouvernance horizontale vise à concrétiser l’engagement du gouvernement fédéral envers les minorités de langue officielle et apparaît comme une forme novatrice d’organisation. Par contre, jusqu’en 2003, elle a aussi servi à compenser l’absence d’action directe et soutenue de la part du gouvernement fédéral envers les minorités de langue officielle. Ce texte étudie et montre comment l’évolution de la gouvernance a suscité des enjeux importants pour le développement de la francophonie en milieu minoritaire.

Société, langue et santé : les barrières à l'accès aux services de santé pour les communautés francophones minoritaires - Consortium national de formation en santé (2e forum national de recherche sur la santé des communautés francophones en situation minoritaire, 2008)

Language proficiency, gender and self-reported health: An analysis of the first two waves of the longitudinal survey of immigrants to Canada - Pottie, Kevin; Ng, Edward; Spitzer, Denise; Mohammed, Alia; Glazier, Richard (Canadian Journal of Public Health, 2008)
Background Most immigrants to Canada now come from Asia, the Middle East, the Caribbean and Africa, where cultures and languages often differ significantly from the Canadian context. Subgroups of immigrants experience disparities in health. Inability to communicate in an official language in Canada may be a marker of risk for poor health due to both pre- and post-migration factors. We aimed to study the relationship between language proficiency and self-reported health. Methods We conducted a cross-sectional analysis of the first two surveys of the Longitudinal Survey of Immigrants to Canada (2001, 2003), a population-based cohort study of new immigrants to Canada. Specifically, we used logistic regression analyses to examine the relationship between self-reported health and language proficiency by sex, controlling for a range of health determinants at 6 months (wave 1) and 2 years (wave 2) after arrival. Results After controlling for covariates (age, sex, education, region of birth, immigrant class, job satisfaction, access to health care), analysis of the wave 1 survey showed that poor proficiency in English or French is significantly related to the self-reported poor health (OR=2.0, p<0.01). And this relationship was consistent in the wave 2 survey (OR=1.9, p<0.01). We also found that this statistically significant association between poor language proficiency and self-reported health holds only for women (wave 1 survey OR=2.6, p <0.01, wave 2 survey OR=2.2, p<0.01), not for men. Conclusion The association between poor language proficiency and poor self-reported health, and particularly its significantly greater impact on women, has implications for language training, health care and social services, and health information.